INVESTIGATION OF DIFFERENT TECHNOLOGY AREAS IN SPORTS IN THE DIMENSION OF ATHLETE MENTAL HEALTH - Akyol, Assoc. Prof. Betül (PEOPLE: International Journal of Social Sciences, 2024)
Sports technologies have been in continuous and uninterrupted ’change and development’ from the day they first started to emerge until today. With each passing year, sports technologies are developing by taking reference from each other through new technologies. With the development of sports technologies, generations, encounter more ’new and advanced’ technologies every day. Sports have an important place in protecting the physical and psychological health of individuals. In addition to physical health, mental health also has an important place in sports. In this respect, the aim of the current research is to examine different technology areas in sports in terms of mental health. For this purpose, as a data collection tool; DergiPark, Higher Education Institution National Thesis Center (YÖKTEZ) and Google Scholar were searched for Turkish sources and Web of Science and PubMed databases for English sources with the keywords "Sport Technology", "Sport Mental Health", "Sport Entertainment" and "Technology Addiction". As a result of the research; it is seen that technology in sports is used for different purposes such as ’entertainment, exercise and performance sports’. In some cases, the use of technology in more equipment or time than needed can create technology addiction in individuals and negatively affect their mental health. On the other hand, it is thought that conscious technology users can transform their existing sports/exercises into an efficient and fun way with sports technologies developed for different purposes. In this respect, it was concluded that, as with all new developing technologies, it is important to determine the needs well when using these technologies and to be a conscious user of sports technologies in terms of mental health.